DAMPAK KOMITMEN MEREK DAN KUALITAS PELAYANAN PADA LOYALITAS TERHADAP BRAND LAYANAN RITEL: Studi Kasus Toko Sinar Kosmetik - Vania Fadhila; Lukman Hakim (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to analyze the impact of brand commitment and consumer loyalty on retail service quality, focusing on cosmetic ray stores. This research method is quantitative. The location of the research was carried out at a cosmetic ray shop located in Surakarta City, Central Java. The population of this study is all consumers of Sinar Cosmetics Stores. The total sample of this study was 150 respondents who were consumers of Sinar Cosmetics Store. The source of this research data is primary data obtained directly through respondents.  Data retrieval technique using google form questionnaire data. The sampling technique uses purposive sampling method. The data analysis technique in this study uses Partial Least Square (PLS) using the help of SMARTPLS Software. The result of this study is that Affective Commitment has a positive and significant influence on Consumer Loyalty. Sustainable Commitment has a positive and significant influence on Consumer Loyalty. Service Quality has a positive and significant influence on Consumer Loyalty